A Comparative analysis between shariah-compliant & non-Shariah compliant stocks / Nurul Syakirah Rifin ... [et al.] - Rifin, Nurul Syakirah; Hassan, Salwana; Abu Bakar, Nordin; Sahudin, Zahariah (Universiti Teknologi Mara Selangor, 2019)
The study reported by this paper investigated the behaviour of stock returns among Shariah-compliant firms and non-Shariah compliant firms of service industry in Malaysia. The data of 50 firms listed in Bursa Malaysia were obtained from 2008 to 2012. It focused on the relationship between the stock returns and the financial ratios (firm size, market to book ratio, price-earnings ratio and total debt) as the microeconomic variables. While the gross domestic product (GDP), interest rate and inflation rate as the macroeconomic variables toward the stock return. Using regression analysis applying OLS technique, the results showed a significant similarity between Shariah-compliant firms and their counterparts. For Shariah-compliant firms, it is found that firm size and total debt is the most significant variables explaining returns, on the other hand, for non-Shariah compliant firms, price-earnings ratio, interest rate and inflation rate are the most significant variables influencing returns.